Immuno-localisations (GSSP) of subcellular accumulation sites of phenanthrene, aroclor 1254 and lead (Pb) in relation to cytopathologies in the gills and digestive gland of the mussel Mytilus edulis - Einsporn, Sonja; Koehler, Angela (Marine environmental research, 2008)
Cell and tissue pathology of both, gill and digestive tissue, has been the subject of many studies for the elucidation of contaminant-induced biological effects. In the present study, cellular pathological alterations were linked to subcellular sites of chemical accumulation in gills and digestive gland tissues. For this purpose, mussels ( Mytilus edulis) were exposed to the organic contaminants aroclor 1254 (PCB) (20 μg/L), phenanthrene (PAH) (150 μg/L) or the metal lead (Pb) (2.5 mg/L). The localization of chemicals at the subcellular level was analysed by an antibody-based detection system (GSSP) by the use of commercially available antibodies specifically directed against the chemicals. Pathological changes were analysed in parallel in identical samples by transmission electron microscopy. After exposure to the different contaminants, cell organelles such as mitochondria, the endo-lysosomal system as well as endoplasmic reticulum showed clear evidence of chemically-induced alterations. Large numbers of crystalloid inclusions were found in mitochondria and in autophagic lysosomes as well as multi-lamellated whorls after PAH and aroclor exposure. Immunocytochemical detection of the chemicals showed their accumulation inside of various cell organelles such as lysosomes, mitochondria, and nuclei. Additionally, chemicals were localized in association to membranes, cilia and microvilli of gill and digestive gland cells. Furthermore, the chitinous rod and mucus secretions of gill epithelial cells were positively labelled for contaminants indicating their role in protection. Localization of contaminants by immuno-detection in combination with pathological diagnosis gives insights into the cellular targets of chemical attack.